Nucleus-Encoded Thylakoid Protein, OsY3IP1, Confers Enhanced Tolerance to Saline and Alkaline Stresses in Rice - Hyeran Moon; Young-Ah Kim; Ryoung Shin; Chang-Jin Park (Rice Science, 2022)
Abiotic stress confers serious damage to the photosynthetic machinery, often resulting in plant growth inhibition. Hypothetical chloroplast open reading frame 3 (Ycf3)-interacting protein 1 (Y3IP1) is a nucleus-encoded thylakoid protein and plays an essential role in the assembly of photosystem I. The full-length cDNA over-expresser (FOX) gene-hunting system is an approach using systemically generated gain-of-function mutants. Among the FOX-rice lines, a line CE175 overexpressing rice Y3IP1 gene (OsY3IP1) displayed less inhibition of root growth under saline (NaCl) stress. The expression of OsY3IP1 was up-regulated under saline and alkaline (Na2CO3) stresses in the rice variety Kitaake. After saline and alkaline treatments, transgenic Kitaake overexpressing OsY3IP1-GFP (OsY3IP1-GFPox/Kit) displayed higher levels of chlorophyll content compared to Kitaake. Under the stress conditions, the maximum quantum yield of photosystem II photochemistry levels was higher in OsY3IP1-GFPox/Kit than in Kitaake. The increased tolerance conferred by OsY3IP1 overexpression correlated with reduced reactive oxygen species accumulation. Our data provide new insights into the possible role of OsY3IP1 in the pathway suppressing photooxidative damage under stress conditions. These features can be further exploited to improve saline and alkaline tolerances of rice plants in future.